Influence of False Self-Presentation on Mental Health and Deleting Behavior on Instagram: The Mediating Role of Perceived Popularity - Mun, Il Bong; Kim, Hun (Frontiers in Psychology, 2021)
The present study explored motivations (need for approval, impression management) for lying self-presentation on Instagram as well as the mental and behavioral outcomes (depression, perceived popularity, deleting behavior on Instagram) of this presentation. We also examined the differential mediational roles of perceived popularity in accounting for the association between lying self-presentation and depression. Our results showed that individuals with a strong need for approval reported higher levels of lying self-presentation. The results also revealed that lying self-presentation positively influenced depression, perceived popularity and deleting behaviors. Furthermore, we found that even if lying self-presentation increased depression, perceived popularity served as a psychological buffer against depression.